Identification of bcl-xl induced micrornas involved in the apoptotic properties of human lung adenocarcinoma cells, a549 / Norahayu Othman - Othman, Norahayu (2012)

(untitled)
Bcl-xL is an anti-apoptotic protein that is frequently found to be overexpressed in lung adenocarcinoma leading to an inhibition of apoptosis and associated with poor prognosis of this disease. Recently, the roles of microRNAs (miRNAs) in regulating apoptosis and cell survival during tumorigenesis have become evident, with cancer cells showing perturbed expression of various miRNAs. In this project, we utilized miRNA microarrays to determine if miRNA dysregulation in bcl-xL silenced A549 lung adenocarcinoma cells could be involved in apoptotic behavior. Data from qRT-PCR and Western blotting indicated that a siRNA-based transfection induced a decrease of bcl-xL expression in A549 cells at both the gene and protein level, resulting in a decrease in cell viability. MiRNA microarray revealed that a total of 10 miRNAs were found to be significantly differentially expressed between bcl-xL silenced A549 cells and non-transfected cells. qRT-PCR validation of the miRNA microarray results indicated that there was a strong positive correlation between the two sets of data. Bioinformatics analysis demonstrated that the differentially expressed miRNAs were found to be involved in several signaling pathways, primarily the PI3K/AKT, intrinsic and extrinsic, WNT, TGF-, and the MAPK pathway. Based on this, a hypothetical pathway illustrating the interactions between these miRNAs with their specific targets were generated describing the effects of bcl-xL silencing on initiation of apoptosis in A549 cells. In conclusion, this study demonstrated that bcl-xL silencing in A549 lung adenocarcinoma cells leads to the occurrence of apoptosis through the dysregulation of specific miRNAs. With further studies carried out to determine the true targets and functions of these miRNAs, our study provided a platform for antisense treatment whereby miRNA expression can be exploited to increase the apoptotic properties in lung adenocarcinoma cells.